A human major histocompatibility complex class I gene that encodes a protein with a shortened cytoplasmic segment. - Geraghty, D E (1987)
We have cloned genomic DNA encoding a non-HLA-A, -B, -C class I gene located within a HindIII-generated restriction fragment of 6.0 kilobase pairs. This gene, designated HLA-6.0, is as homologous to HLA-A and HLA-B as they are to each other. The HLA class I protein encoded by HLA-6.0 is similar in organization to the HLA-A-, -B-, and -C-encoded proteins except that an in-frame termination codon prevents translation of a majority of the cytoplasmic region of the HLA-6.0 polypeptide. Moreover, the promoter region of HLA-6.0 resembles the promoter region of a Qa region gene. These structural features of HLA-6.0 suggest that this non-HLA-A, -B, -C gene is a structural homolog of a murine Qa region class I gene.